The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/508039
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Incident Clearance Time and Arrival Time Prediction Based on Hazard Models

Abstract: Accurate prediction of incident duration is not only important information of Traffic Incident Management System, but also an effective input for travel time prediction. In this paper, the hazard based prediction models are developed for both incident clearance time and arrival time. The data are obtained from the Queensland Department of Transport and Main Roads' STREAMS Incident Management System (SIMS) for one year ending in November 2010. The best fitting distributions are drawn for both clearance and arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…As such, much effort has been devoted to understanding the factors that contribute to truck-involved crashes and crash outcomes. Considering that crash incident clearance time is significantly impacted by the crash severity ( Ding et al., 2015 ; Islam et al., 2021 ; Ji et al., 2014 ), this study contributes to this effort by exploring differences and similarities in crashes involving in-state and out-of-state truck drivers. It is worth noting that a preliminary analysis of the data used in the study showed similar proportions of crashes involving in-state and out-of-state drivers across the years.…”
Section: Discussionmentioning
confidence: 99%
“…As such, much effort has been devoted to understanding the factors that contribute to truck-involved crashes and crash outcomes. Considering that crash incident clearance time is significantly impacted by the crash severity ( Ding et al., 2015 ; Islam et al., 2021 ; Ji et al., 2014 ), this study contributes to this effort by exploring differences and similarities in crashes involving in-state and out-of-state truck drivers. It is worth noting that a preliminary analysis of the data used in the study showed similar proportions of crashes involving in-state and out-of-state drivers across the years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found various statistical modeling methods to be appropriate for examining incident clearance times. ese models include simple regression models [29], switching regression models [30], quantile regression models [2,31], hazard-based duration models [32][33][34][35][36][37][38], accelerated failure time (AFT) models [33,39,40], finite mixture models [41], generalized F distribution models [42], artificial neural network models [43], and Bayesian network models [44]. Hazard-based duration models have been found to be more appropriate in examining duration data [32,45,46]; therefore, in this paper, random parameters hazard-based duration models were employed to identify contributing factors of incident clearance time.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, survival models are being used for various transport applications such as incident detection [27][28][29], arrival time modelling [19], incident and arrival time [30], driver distraction [31][32][33], service time estimation [34], urban traffic congestion duration modelling [35], accident duration modelling [36], urban arrival times analysis [37], choice of car-share vehicle [38] and so on. Hazard-based methods have been applied to many transportation applications (including arrival times and travel time) [37].…”
Section: Literature Reviewmentioning
confidence: 99%